Maximum insulin dose in patients admitted to the intensive care units with severe COVID‐19 in the “Cross ICU Searchable Information System” study: A multicenter retrospective cohort study - Emi Ushigome; Dan Imai; Masahide Hamaguchi; Satoru Hashimoto; Michiaki Fukui (Journal of Diabetes Investigation)
ABSTRACT Aims This study aimed to determine the maximum daily insulin dose (MDI) and associated factors in critically ill patients with coronavirus disease 2019 (COVID‐19) receiving insulin therapy, under ventilator and/or extracorporeal membrane oxygenation (ECMO) management. Materials and Methods This cross‐sectional analysis used the Cross ICU Searchable Information System data from a Japanese multicenter retrospective observational cohort study of critically ill patients with COVID‐19 receiving ventilation and/or ECMO, from February 2020 to March 2022. Maximum daily insulin dose was determined, and factors associated with it and maximum daily insulin dose per body weight were assessed using linear regression analysis. Results The analysis included 788 patients. Their mean age, glycated hemoglobin level, maximum daily insulin dose, and time from admission to the maximum daily insulin dose were 65.2 ± 13.0 years, 7.0 ± 1.5% (53.0 ± 7.1 mmol/mol), 46.0 ± 43.6 U/day, and 7.3 ± 7.0 days, respectively. Male sex (β = 6.902, P = 0.034), body mass index (β = 1.020, P = 0.001), glycated hemoglobin (β = 12.272, P < 0.001), and having renal failure (β = 20.637, P = 0.003) were independent determinants of maximum daily insulin dose. Age (β = 0.004, P = 0.035), glycated hemoglobin (β = 0.154, P < 0.001), and having renal failure (β = 0.282, P = 0.004) were independent determinants of maximum daily insulin dose per body weight. Conclusions In patients with COVID‐19 on ventilator and/or ECMO management, the maximum daily insulin dose reached after about 1 week of hospitalization was approximately 46.0 U/day. Glycated hemoglobin and renal failure were both associated with the maximum daily insulin dose and maximum daily insulin dose per body weight.